2008
DOI: 10.1027/1015-5759.24.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Method-Specific Variance in the IAT

Abstract: The present paper introduces a new variant of the Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998 ) called the Single Block IAT (SB-IAT). By eliminating the IAT’s block structure, the SB-IAT is argued to solve the structural problem of recoding in the IAT and accordingly, its contamination by method-specific variance. In Study 1, a flower-insect SB-IAT, a task-switching ability SB-IAT, and a geometry SB-IAT showed reduced, but still significant effects. Zero correlations between the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 26 publications
(74 reference statements)
1
79
0
Order By: Relevance
“…Also, substantial implicitÁimplicit correlations can be expected. Finally, this domain has often been used to validate indirect measures (e.g., Payne, Cheng, Govorun, & Stewart, 2005; Teige-Mocigemba, Klauer, & Rothermund, 2008). Specifically, as fake prime categories, we selected ''Alliance 90/ The Greens'' (referred to as the Greens in the following) and the ''Christian Democratic Union'' (referred to as CDU in the following).…”
Section: Methodsmentioning
confidence: 99%
“…Also, substantial implicitÁimplicit correlations can be expected. Finally, this domain has often been used to validate indirect measures (e.g., Payne, Cheng, Govorun, & Stewart, 2005; Teige-Mocigemba, Klauer, & Rothermund, 2008). Specifically, as fake prime categories, we selected ''Alliance 90/ The Greens'' (referred to as the Greens in the following) and the ''Christian Democratic Union'' (referred to as CDU in the following).…”
Section: Methodsmentioning
confidence: 99%
“…7 The discovery of method related variance on IAT effects has led to the emergence of a second generation of IAT alternatives that aim to circumvent the block structure of the task and its relativistic nature. Examples include the Single Block IAT (Teige-Mocigemba, Klauer, & Rothermund, 2008), Recoding Free IAT (Rothermund et al, 2009) and the Sorting Paired Features Task (Bar-Anan, Nosek, & Vianello, 2009). Equally, a number of strategies have also been devised to reduce method variance on sematic and evaluative priming tasks (see Wentura & Degner, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that task-switching costs (greater costs, i.e., slower responses, in tasks pairing categories that are not well associated) represent an important component of the IAT effect (Mierke & Klauer, 2001, 2003. Additionally, individual differences in task-switching ability were shown to represent a small portion of method-specific IAT variance that was independent of the associations being measured (Back, Schmukle, & Egloff, 2005; Teige-Mocigemba, Klauer, Rothermund, 2008).…”
Section: Accounts For the Iat Effectmentioning
confidence: 99%